Análisis semiótico de los siete pecados capitales según la película ‘Seven’ de David Fincher - Llosa Rios, Carolina (2018)
In this article, we will present a semiotic analysis of the seven deadly sins in David Fincher’s film Se7en, focusing on the concepts of savior and sinner. The different meanings assigned to our subject matter will be contrasted against the dichotomic concepts of good and evil. To carry out this analysis, we will employ the tools of structural semantic analysis and semiotic square. The first tool will be used to classify the meanings given to each of the seven sins, whereas the second will help demonstrate the movement along the ideas of savior and sinner of the representatives of the two most important sins.